The p38 mitogen‐activated protein kinase cascade modulates T helper type 17 differentiation and functionality in multiple sclerosis. Issue 2 (6th July 2015) - Di Mitri, Diletta; Sambucci, Manolo; Loiarro, Maria; De Bardi, Marco; Volpe, Elisabetta; Cencioni, Maria Teresa; Gasperini, Claudio; Centonze, Diego; Sette, Claudio; Akbar, Arne N.; Borsellino, Giovanna; Battistini, Luca
Summary: The p38 mitogen‐activated protein kinase cascade is required for the induction of a T helper type 17 (Th17) ‐mediated autoimmune response, which underlies the development and progression of several autoimmune diseases, such as experimental autoimmune encephalomyelitis, the animal model of multiple sclerosis (MS). However, the contribution of p38 phosphorylation to human Th cell differentiation has not been clarified. Here we demonstrate that the p38 signalling pathway is implicated in the generation of Th17 lymphocytes from human CD4 + CD27 + CD45RA + naive T cells, both in healthy donors and in patients affected by the relapsing–remitting form of MS. Our data also indicate that p38 activation is essential for interleukin‐17 release from central memory lymphocytes and committed Th17 cell clones. Furthermore, CD4 + T cells isolated from individuals with relapsing–remitting MS display an altered responsiveness of the p38 cascade, resulting in increased p38 phosphorylation upon stimulation. These findings suggest that the p38 signalling pathway, by modulating the Th17 differentiation and response, is involved in the pathogenesis of MS, and open new perspectives for the use of p38 inhibitors in the treatment of Th17‐mediated autoimmune diseases.